1996
DOI: 10.1093/jn/126.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Lysyl Oxidase by Dietary Copper in Rats

Abstract: Lysyl oxidase levels were estimated in rat tissues using an enzyme-linked immunosorption assay (ELISA) and a functional assay standardized against known amounts of purified lysyl oxidase. High concentrations of lysyl oxidase (> or = 150 micrograms/g of tissue or packed cells) were detected in connective tissues, such as tendon and skin. Values for aorta, kidney, lung and liver ranged from 30 to 150 micrograms/g of tissue; values for skeletal muscle and diaphragm were < 30 micrograms/g tissue. Purified rat skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“…Severe Cu deficiency resulted in decreased crosslinking of connective tissue, consistent with decreased function of LO [39] . Enzyme activity levels were decreased in the skin of weanling rats fed with a copper deficient diet [40] . Exogenously added Cu has been shown to elevate LO activity and LO mRNA levels in cultured RFL6 cells [41] .…”
Section: Discussionmentioning
confidence: 96%
“…Severe Cu deficiency resulted in decreased crosslinking of connective tissue, consistent with decreased function of LO [39] . Enzyme activity levels were decreased in the skin of weanling rats fed with a copper deficient diet [40] . Exogenously added Cu has been shown to elevate LO activity and LO mRNA levels in cultured RFL6 cells [41] .…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies of Cu deficiency in rats (Robins et al 1985;Farquharson et al 1989) showed significant effects on bone collagen cross-links only after a prolonged and severe deficiency, which produced a major decrement in body-weight gain, amonst other deleterious effects. The current consensus, therefore, seems to be that, in laboratory rodents at least, Cu deficiency needs to be both prolonged and severe before the activity of the Cu-dependent enzyme, lysyl oxidase, is impaired sufficiently to cause any significant effects on mature bone collagen cross-linking (Rucker et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The catalytic activity of LOX is copper-dependent with the carboxyterminus requiring the presence of a tightly bound active copper (II) ion (30). Although copper availability does not directly affect synthesis, it does markedly influence its functional activity (31,32). Tetrathiomolybdate is a potent copper chelator and has demonstrated antiangiogenic, antifibrogenic, and anti-inflammatory actions in preclinical studies.…”
Section: Therapeutic Potential and Clinical Implications For Future Tmentioning
confidence: 99%